Narration and Experience: Looking at an Education based on “Poor” Pedagogy – an Analysis based on a Learning-to-Write Situation - Leite, César Donizetti Pereira (Acolhendo a Alfabetização nos Países de Língua Portuguesa, 2014)
With an approach that designates the classroom as its central reference point and a concrete classroom situation as its starting point, this paper attempts to reflect a perspective that may suggest a teaching practice that leads to poor pedagogy. To achieve this, this paper will work on inverting the logic we frequently employ when thinking about education and school. From this perspective, some axes become central: (1) to produce a view about the idea of knowledge and learning, (2) an awareness of a certain notion of “to teach” and finally (3) starting from a focus on the type of childhood that creates a necessity of “infantilizing” pedagogy, or in other words, we must aim towards a “poor” pedagogy. I will address this through a study carried out with children in the initial stages of their education and literacy learning.